Arbuscular mycorrhiza differentially adjusts central carbon metabolism in two contrasting genotypes of Vigna radiata (L.) Wilczek in response to salt stress - Sharma, Karuna (Plant science : an international journal of experimental plant biology, 2023)
Copyright © 2023 Elsevier B.V. All rights reserved.